Schwannoma of the medial cutaneous nerve of the arm: a rare location with concomitant compression neuropathy of the ulnar nerve - Gosk, Jerzy; Gutkowska, Olga; Martynkiewicz, Jacek; Bąk, Michał; Hałoń, Agnieszka (Folia Neuropathologica, 2015)
The objective of this paper is to present a case of rare location of schwannoma in the medial cutaneous nerve of the arm at the level of the axilla. Preliminary diagnostic examination of the tumour was carried out in another hospital by means of open biopsy. In the preoperative period symptoms of ulnar nerve dysfunction (paraesthesias, positive Hoffmann-Tinel sign) dominated the clinical picture. After having performed imaging studies and electromyographic (EMG) examination, the patient was scheduled for an operation. The tumour, measuring 3.5 × 3.0 × 1.5 cm, was resected without damage to the fascicular structure. Presence of paraesthesias in the distribution of the medial cutaneous nerve of the arm, which was first noted in the postoperative period, persists in moderate severity until now. As a result of the performed operative treatment, such symptoms as palpable tumour mass, pain, paraesthesias in the ulnar nerve distribution and positive Hoffmann-Tinel sign resolved. On the basis of histopathological examination results the final diagnosis of classical schwannoma was established.